THE INFLUENCE OF DIFFERENTIATION STRATEGY TOWARDS BUYING DECISION ON SAMSUNG GALAXY SMARTPHONE WITH CONSUMER PERCEIVED VALUE AS A MEDIATING ROLE IN MANADO CITY - Kaban, Zakariya U.; Kindangen, Paulus; Tumewu, Ferdinand J. (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2021)
The purpose of this research is to measures the effectiveness of differentiation strategy of brand Samsung on buying decision with the contribution of consumer perceived value. This research is a type of causal study since the purpose is to determine if one or more variables cause another variable to occur or change. This research is a quantitative method with a questionnaire as a tool to gather data and analysis Burns and Bush (2006:202) stated quantitative Research is defined as research involving the use of structured questions in which the response options have been predetermined and a large number of respondents is involved. The results of conducted test based on a questionnaire filled out by respondents stated that Samsung smartphone promotions were classified as good with an average of 3.86. Differentiation Strategy has a positive and significant influence on the Perceived Value on smartphone owners of the Samsung brand, this could be occurred because of Samsung's strategy providing differentiation in design so as to make the owners feel like they get more value as an upper-class smartphone user. Based on the results of the test, analysis, and discussion researcher found the differentiation strategy does not significantly influence Samsung smartphone purchase decisions if itâ€™s not through value perception.Â Keywords: differentiation strategy, buying decision, consumer perceived value, samsung, path analysis